Impact of organic solvent additive on the integrity of plasma samples in bioanalysis by LC–MS/MS. (October 2013) - Dicaire, Catherine; Mess, Jean-Nicholas; Furtado, Milton; Bergeron, Annik; Garofolo, Fabio
Background: Matrix effects are one of the major drawbacks of ESI–MS/MS. It is majorly caused by lipids in plasma, which can be overcome by using different extraction techniques.Results: In this investigation, a major matrix effect was observed in samples containing a co-administered drug. Unknown compounds appeared over time in the human plasma samples spiked with co-administered drug creating major ion suppression. The changes in matrix integrity were associated with the organic solvent content in the plasma samples.Conclusion: The amount and type of organic solvent added to human plasma along with the storage conditions must be carefully determined during method development in order not to impact quantitation.